2011
DOI: 10.1007/s11837-011-0073-7
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of acquiring a thermal analysis cooling curve by wet sample cup made of green sand

Abstract: How would you……describe the overall significance of this paper?In traditional thermal analysis applied in foundry, dry sample cups made of resin-bonded sands are widely used. If the cups could be made of green sand, traditional dry sample cups could be replaced and thus reduce costs and emissions of irritating gases. The purpose of this study is to determine whether it is feasible to acquire the cooling curve with obvious characteristic points by the wet sample cups made of green sand.…describe this work to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Through comparative testing of each cup type to gage repeatability and reproducibility, it was concluded that when the cups are used for real-time control of the respective carbon equivalent, carbon, and silicon contents of ductile base iron, the "round and plain" and "square and tellurium" cups perform superiorly to the "round and tellurium" and "square and plain" cups. Shi et al [19] studied the feasibility of achieving cooling curves with obvious characteristic points using a wet sample cups made of green sand. Taking full consideration of the thermocouple position in addition to the volume and thickness of the sample cups, a set of molds was designed to make wet sample cups of differing dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Through comparative testing of each cup type to gage repeatability and reproducibility, it was concluded that when the cups are used for real-time control of the respective carbon equivalent, carbon, and silicon contents of ductile base iron, the "round and plain" and "square and tellurium" cups perform superiorly to the "round and tellurium" and "square and plain" cups. Shi et al [19] studied the feasibility of achieving cooling curves with obvious characteristic points using a wet sample cups made of green sand. Taking full consideration of the thermocouple position in addition to the volume and thickness of the sample cups, a set of molds was designed to make wet sample cups of differing dimensions.…”
Section: Introductionmentioning
confidence: 99%